Breast cancer polygenic risk scores in the clinical cancer genetic counseling setting: Current practices and impact on patient management. Issue 2 (30th October 2020) - McGuinness, Molly; Fassi, Emily; Wang, Catharine; Hacking, Claire; Ellis, Victoria
Abstract: Multivariate risk models are commonly used in clinical practice to estimate a woman's lifetime risk for breast cancer and assist in implementation of appropriate screening and risk reduction strategies. More recently, breast cancer polygenic risk scores (PRS) have been derived and integrated into these models to further improve risk estimation. While breast cancer PRS have been offered by two clinical diagnostic laboratories since 2017, little is known about the extent to which genetic counselors are ordering breast cancer PRS or incorporating the results into patient management. This study surveyed U.S. cancer genetic counselors from October 2019 to January 2020 to identify and understand their current practices with breast cancer PRS, to determine the impact of breast cancer PRS on patient management, and to anticipate future genetic counselor practices with breast cancer PRS. Fewer than half of respondents (43%, 51/120) had ordered breast cancer PRS and approximately one‐third (35%, 16/46) reported that the PRS had changed their medical management recommendations. The majority of cancer genetic counselors had not ordered PRS, most commonly due to (a) lack of clinical guidelines (90%, 60/67), (b) insufficient evidence of clinical utility (88%, 59/67), and (c) lack of availability for patients of non‐European ancestry (70%, 47/67). Of genetic counselors who had not ordered breast cancer PRS, only 10% (7/68) did not believe they would order PRS in the future. This is the first study to characterize genetic counselors' experiences with breast cancer PRS. Results from this study indicate that although breast cancer PRS have been clinically available for patients for several years, most cancer genetic counselors are not yet convinced they are ready to be incorporated into patient care.